New Method for Preparation of Nano Alumina Powder Using Aluminum(III) Complexes by Combustion Synthesis Without Fuel - Z. Khoshkhan; M. Salehi (Journal of Nanostructures, 2014)
Alumina nanomaterials were synthesized via a solution combustion technique using tris-(acetylacetonato) aluminum(III) complex (1) and tris-(2-formylphenolate) aluminum(III) complex (2) at 600, and 1000 °C for 3h. The obtained data showed that the procedure without using fuel resulted in a better phase and morphology. To investigate the phase formation, powder X-ray diffraction technique was used. Also, FESEM micrographs were used to investigate the morphology of the obtained materials. It showed that the morphology of the obtained materials was in the form of different types of porous and particle materials. The optical properties of the obtained materials were studied by FTIR spectra. According to the data, it was found that with annealing at 600 °C, the phase formation of the obtained materials showed cubic crystal structures with cell parameter a =  3.14 Å for gamma phase. With increasing the annealing temperature to 1000 °C, the obtained material was found to be in a mixture of orthorhombic and hexagonal crystal structures.